2017
DOI: 10.1016/j.jaip.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Risk of Future Asthma Attacks Using UK Medical Record Data: A Respiratory Effectiveness Group Initiative

Abstract: Background: Asthma attacks are common, serious, and costly. Individual factors associated with attacks, such as poor symptom control, are not robust predictors. Objective: We investigated whether the rich data available in UK electronic medical records could identify patients at risk of recurrent attacks. Methods: We analyzed anonymized, longitudinal medical records of 118,981 patients with actively treated asthma (ages 12-80 years) and ≥3 years of data. Potential risk factors during 1 baseline year were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
85
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(96 citation statements)
references
References 38 publications
6
85
2
3
Order By: Relevance
“…found that prior acute care visits for asthma predicted subsequent acute care visits with an AUC of 0.75, after adjustment for age, sex, race, and insurance status, and the association between prior ED visits and subsequent ED visits for asthma has been shown elsewhere as well . One study using a clinical score found an AUC of 0.75 for predicting exacerbation, and a very complex model utilizing multiple clinical risk factors had an AUC of 0.87 for predicting four or more asthma attacks in 2 years . Given that the current study was limited to administrative data, the AUCs of 0.70–0.76 are consistent with, or a slight improvement on, prior results.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…found that prior acute care visits for asthma predicted subsequent acute care visits with an AUC of 0.75, after adjustment for age, sex, race, and insurance status, and the association between prior ED visits and subsequent ED visits for asthma has been shown elsewhere as well . One study using a clinical score found an AUC of 0.75 for predicting exacerbation, and a very complex model utilizing multiple clinical risk factors had an AUC of 0.87 for predicting four or more asthma attacks in 2 years . Given that the current study was limited to administrative data, the AUCs of 0.70–0.76 are consistent with, or a slight improvement on, prior results.…”
Section: Discussionmentioning
confidence: 59%
“…Previously reported predictive models for asthma‐related health care utilization have used heterogeneous samples with varying amounts of clinical and administrative data. Multiple models have found that prior ED or hospital utilization is predictive of subsequent use . However, many models used information about previous prescriptions or detailed prior history and laboratory testing that are unlikely to be available to an ED provider, limiting their clinical utility.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1012] Interrogation of EMRs has also revealed the potential value of routinely recorded data to identify and validate the use of existing and exploratory biomarkers (e.g. blood eosinophils, FeNO [existing]; exhaled breath condensate markers [proposed]).…”
Section: Emerging Opportunities: Risk Reduction and Biomarkersmentioning
confidence: 99%
“…When assessing asthma outcomes amongst people with OUD, it is important to acknowledge this group are more likely to be male, come from areas of high deprivation and have smoking histories 5 . Factors such as these have been shown to influence asthma outcomes including exacerbation rates [21][22][23][24] . This study, aims to assess asthma care and outcomes amongst asthma patients with a history of OUD in a large primary care population after controlling for such confounding.…”
Section: Introductionmentioning
confidence: 99%